2013
DOI: 10.1111/imm.12105
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of IL‐17 induction by Schistosoma japonicum infection in C57BL/6 mouse liver

Abstract: SummarySchistosomiasis japonica is a severe tropical disease caused by the parasitic worm Schistosoma japonicum. Among the most serious pathological effects of S. japonicum infection are hepatic lesions (cirrhosis and fibrosis) and portal hypertension. Interleukin-17 (IL-17) is a pro-inflammatory cytokine involved in the pathogenesis of many inflammatory and infectious conditions, including schistosomiasis. We infected C57BL/6 mice with S. japonicum and isolated lymphocytes from the liver to identify cell subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 48 publications
2
75
2
Order By: Relevance
“…Our results showed that Sm-p80 vaccine formulated in GLA-SE induced mixed Th1 (IFN-γ, TNF-α, IL-2 and IL-12) and Th2-type immune responses which appeared to correlate with the cross-species protection observed in this S. japonicum model of infections which was in agreement with our previous studies on S. mansoni infection models (Karmakar et al 2014a; Karmakar et al 2014b). The downregulation of IL-17 observed in the S. japonicum /mouse studies (Trials 1 and 2) might not be entirely non-beneficial as studies have shown that blocking IL-17 cytokine production in S. japonicum -infected mice resulted in the reduction of granuloma formation and fibrosis (Chen et al 2013; Zhang et al 2012). Th1 and Th2 cytokines regulation in the vaccinated hamsters followed similar pattern as those in the S. japonicum infection models as we observed upregulation of Th1 cytokines (IFN-γ, TNF-α and IL-12) and Th2 cytokines (IL-4, IL-10 and IL-13) in vaccinated animals (Fig 7C and D).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that Sm-p80 vaccine formulated in GLA-SE induced mixed Th1 (IFN-γ, TNF-α, IL-2 and IL-12) and Th2-type immune responses which appeared to correlate with the cross-species protection observed in this S. japonicum model of infections which was in agreement with our previous studies on S. mansoni infection models (Karmakar et al 2014a; Karmakar et al 2014b). The downregulation of IL-17 observed in the S. japonicum /mouse studies (Trials 1 and 2) might not be entirely non-beneficial as studies have shown that blocking IL-17 cytokine production in S. japonicum -infected mice resulted in the reduction of granuloma formation and fibrosis (Chen et al 2013; Zhang et al 2012). Th1 and Th2 cytokines regulation in the vaccinated hamsters followed similar pattern as those in the S. japonicum infection models as we observed upregulation of Th1 cytokines (IFN-γ, TNF-α and IL-12) and Th2 cytokines (IL-4, IL-10 and IL-13) in vaccinated animals (Fig 7C and D).…”
Section: Discussionmentioning
confidence: 99%
“…Th-17 cells play an important role in host defence against infection. In parasitic infection, however, IL-17 has been described in both protective (26) and pathologic contexts (27,28). For example, IL-27R-deficient mice infected with Toxoplasma gondii and Leishmania major develop severe disease that is characterized by a prominent IL-17 response (24).…”
Section: Discussionmentioning
confidence: 99%
“…These cells primarily colonize in the mucosa and skin where they play an important role in immune regulation 4. γδT cells have been suggested to mediate inflammatory cell infiltration and remodeling in a murine model via interleukin (IL)-17A, which has been proven to be a crucial regulator of cardiac fibrosis 5678. However, the links between γδT cells, inflammation and tissue remodeling in CRS appear to be unknown.…”
Section: Introductionmentioning
confidence: 99%